2009
DOI: 10.1017/s1742170509002580
|View full text |Cite
|
Sign up to set email alerts
|

New roller crimper concepts for mechanical termination of cover crops in conservation agriculture

Abstract: Rollers crimpers have been used in conservation agriculture to terminate cover crops; however, excessive vibration generated by the original straight-bar roller design has delayed adoption of this technology in the United States. To avoid excessive vibration, producers generally reduce operating speeds that increase the time needed to perform the field operation. The objectives of this research were to identify roller crimper designs that terminated rye cover crops consistently, resulted in soil moisture conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 9 publications
4
54
0
Order By: Relevance
“…The two researchers concluded that small-grain cover crops could be killed effectively if rolling-crimping was delayed until advanced growth stages (Zadoks growth stage, ZGS 85; [30]). Recent roller-crimper designs have improved efficacy of killing cover crops and enhanced operator comfort when used in the field [31][32][33]. Current models can kill over 90% of a rye cover crop when terminated as early as 50% anthesis or ZGS 65 in some environments [34].…”
Section: Organic Zero Tillagementioning
confidence: 99%
“…The two researchers concluded that small-grain cover crops could be killed effectively if rolling-crimping was delayed until advanced growth stages (Zadoks growth stage, ZGS 85; [30]). Recent roller-crimper designs have improved efficacy of killing cover crops and enhanced operator comfort when used in the field [31][32][33]. Current models can kill over 90% of a rye cover crop when terminated as early as 50% anthesis or ZGS 65 in some environments [34].…”
Section: Organic Zero Tillagementioning
confidence: 99%
“…A roller-crimper is a ground-driven implement that physically terminates near-mature cover crops before no-till cash crop planting, leaving a surface mulch of cover crop shoot residues as well as intact belowground root residues (Ashford and Reeves 2003;Reberg-Horton et al 2012;Wells et al 2013). Used for many years in Brazil (Derpsch et al 1991), roller-crimping cover crops in annual row-crop systems increased in popularity in the US following improvements in roller-crimper design (Kornecki et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Scientists are exploring cultural tactics to reduce intensity of tillage (Peigne et al 2007;Maader and Berner 2012). Methods such as strip tillage (Brainard et al 2013) or a crimper-roller that mechanically kills cover crops (Kornecki et al 2009) have been developed. These methods have led to a concept of rotational tillage, where reduced or no-till sequences are integrated within a longer tillage-based rotation (Legere et al 2013).…”
Section: Introductionmentioning
confidence: 99%